2019
DOI: 10.1016/j.jadohealth.2018.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Gender Inequality and Sex Differences in Physical Fighting, Physical Activity, and Injury Among Adolescents Across 36 Countries

Abstract: Purpose: Sex differences in adolescent health are widely documented, but social explanations for these sex differences are scarce. This study examines whether societal gender inequality (i.e., men's and women's unequal share in political participation, decision-making power, economic participation and command over resources) relates to sex differences in adolescent physical fighting, physical activity, and injuries.Methods: National-level data on gender inequality (i.e. the United Nations Development Program's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
51
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 26 publications
9
51
1
2
Order By: Relevance
“…Regarding the intensity of PA, it was found that men present higher values than women in relation to HPA. Similar data are found in several studies carried out on university students [60][61][62]. Likewise, men obtained higher results than women in relation to SPA.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding the intensity of PA, it was found that men present higher values than women in relation to HPA. Similar data are found in several studies carried out on university students [60][61][62]. Likewise, men obtained higher results than women in relation to SPA.…”
Section: Discussionsupporting
confidence: 90%
“…22 The transition to adulthood is a period of increased risk of injury. 23 Boys reported more physical activity injuries than girls, 24 as well as more intentional injury. 8 Unlike unintentional injuries, girls with self-injury=suicide report rates and frequency of occurrence higher than boys, 25 but a meta-analysis in China found no gender difference in the prevalence of non-suicidal self-injury in urban areas among secondary school students.…”
Section: Discussionmentioning
confidence: 94%
“…One of the explanatory factors of gender differences in medically attended injuries is societal gender inequality, which was recently positively associated with sex differences in adolescent injuries, physical fighting, and physical activity by de Looze et al [ 28 ]. According to them, in all studied countries, boys reported more physical fighting, physical activity, and injuries than girls, but the magnitude of these sex differences varied greatly between countries.…”
Section: Discussionmentioning
confidence: 99%
“…There can be various reasons why adolescents engage in fighting, such as self-defense, to gain or maintain respect, or anger, which can be addressed using various prevention strategies, including interventions that teach anger management and conflict resolution, that promote adolescent self-efficacy in using nonviolent strategies, and that address parental attitudes about fighting [ 34 ]. The effectiveness of such strategies and the search for other risk factors of this risk behavior should guide the future research in this largely neglected area of global health research [ 28 , 30 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%